Plasmonic Waveguides for Sub-wavelength Light Confinement - ZHONG, CHUAN (Trinity College Dublin. School of Physics. Discipline of Physics, 2018)
Modern electronic devices and circuits for information processing are rapidly approaching their ultimate speed and bandwidth limitations, which is an increasingly serious problem that impedes their continued use in scientific and technological applications. One promising solution is believed to be integrating electronic and photonic components on the same chip. This technology provides large bandwidth which can be used to design novel broadband electronic photonic devices. However, a major problem with using electromagnetic waves as information carriers in optical integrated circuits is the low level of integration and miniaturization, which are not at the same scale as modern electronics. This is a consequence of the diffraction limit of light in a dielectric medium, an optical principle that sets a lower limit on how much the cross-section of light can be reduced based on the refractive index of the material, which restricts the light waves being confined to nanoscale regions much smaller than its wavelength. Therefore, other approaches of guiding light at sub-wavelength scale have to be found. One possible solution is using surface plasmon polaritons (SPP), which can achieve sub-wavelength scale light confinement and highly localized electromagnetic field intensity. The particular integrated electronicphotonic technology which motivates this work is heat-assisted magnetic recording (HAMR) technology, which has the potential to be the driving force in the next generation of magnetic storageminiaturization. This technology combines a conventional electronic device, a perpendicular magnetic recording (PMR) read/write head, with a dielectric photonic waveguide and a plasmonic focusing element. There are a number of technical issues which must be overcome in order for this technology to become commercially viable. In this thesis, both the theoretical and the experimental work on plasmonic focusing elements for subwavelength light confinement is presented. We experimentally excite SPP through a Kretschmann-Raether configuration, and use this platform to map the dispersion of SPP in thin Ag-Au films or varying composition. The second part of this thesis deals with the design of a nearfield transducer (NFT) for HAMR. This requires design and fabrication of a nanoscale tip in which a plasmonic response is generated to write bits with size below 50 nm by 50 nm. Furthermore, the incident optical energy must be guided to the plasmonic NFT using an integrated dielectric waveguide. We design an evanescent coupling system to efficient extract the incident light from the dielectric waveguide core to the NFT. Our design is larger scale than other proposed designs, resulting in easier fabrication, better thermal stability and better extinction of undesired optical energy continuing in the dielectric waveguide. The coupling process is optimized to maximize the electromagnetic intensity in the NFT while minimizing intensity remaining in the dielectric waveguide to avoid the miswriting of a magnetic bit in the recording medium. The final research topic includes improving the plasmonic performance of Au film. Investigations involve using an Ag-Cu-Au combined film to achieve a tunable dispersion property which can produce a superior plasmonic performance. Moreover, thin metallic layers as adhesion and capping layers will improve the excitation of the SPP mode of the NFT without degrading plasmonic performance when excited by strong optical field.
APPROVED
Keywords: Surface plasmon polaritons; Plasmonic waveguides; Sub-wavelength light confinement; Near-field transducer.